PENGARUH PENDIDIKAN KESEHATAN DAN KONSUMSI AIR REBUSAN DAUN SALAM TERHADAP PENGENDALIAN ASAM URAT - Sri Wahyuni Adriani; Mardiana Firdausi; Devry Eka Wahyudi; Fitri Dwi Anggraeni; Gunawan Tri Sutrisno; Zehrotul Jannah; Muhammad Nuryasin (JURNAL KESEHATAN MERCUSUAR, 2021)
Healthy lifestyle is an indicator and influence on health problems. Self-management in dealing with this must be done productively. When uric acid is produced in excess and the processing of uric acid is decreased, uric acid levels in the blood are higher. To overcome this, non-pharmacological treatment can be done by consuming bay leaves boiled water. In addition, health education is also needed. Health education is one of the effective nursing interventions to increase awareness and knowledge. This study aims to determine the effectiveness of uric acid health education and drinking bay leaf boiled water to control gout. The research method used is pre-experimental design with pre-posttest design approach. The population was 60 respondents. The sampling method included home visits to gout sufferers. The sample was 22 respondents. Wilcoxon test was used for statistical tests. The results of the pre-posttest showed the P value was 0.001, which is less than 0.05. In other words, health education and consumption of bay leaf water effectively reduce uric acid levels. This research is recommended for the whole community because this intervention has minimal side effects, materials and tools are easy to obtain, and cost-effective so that it can be applied independently